A Note on Gilbert Sheldon - Higham, Florence (The journal of ecclesiastical history, 1963)
In 1883 Osmund Airy published in the British Quarterly Review some ‘Notes on the reign of Charles II’, in which he stressed the fear of popery still felt by the average Englishman. He instanced this by describing the feelings aroused by the king's issue of an Indulgence in December 1662. ‘Charles’, he wrote, ‘was not long left in ignorance of the feelings he had roused … The meeting, as we should say, spoke at once through its chairman’. ‘We were fortunate enough some while ago’, Airy continues, ‘while searching in the British Museum on this subject, to find a letter which we believe has not anywhere been noticed, addressed to the King by the Archbishop of Canterbury, Gilbert Sheldon, who appears to represent completely the savage side of the Anglican Church’. Airy proceeded to quote the letter in full, noting ‘this is written within three months after the proposal for comprehension, probably in January’. The letter is violent in tone, referring, for instance, to ‘that most damnable and heretical doctrine of the Church of Rome, whore of Babylon’, and warning the king that by his action he may draw upon himself and the kingdom in general ‘God's heavy wrath and indignation’. A number of later historians have followed Airy in attributing the letter to Sheldon, though not without surprise at the unlikely language.